Immobilization of silver nanocrystals on carbon nanotubes using ultra-thin molybdenum sulfide sacrificial layers for antibacterial photocatalysis in visible light. (January 2016) - Liu, Wenhong; Feng, Yi; Tang, Huawei; Yuan, Huaibo; He, Shuai; Miao, Shiding
Abstract: A new method is developed to immobilize silver (Ag) nanocrystals (NCs) on carbon nanotubes (CNTs) by using the pre-coated MoS2 as sacrificial layers, and a type of composite materials consisting with CNTs, Ag NCs and MoS2 have been prepared. In this method the ultral-thin layers of MoS2 are coaxially pre-coated on the CNTs to prepare the hybrid of CNTs-MoS2 . The CNTs-MoS2 is used as substrates to immobilize Ag NCs in a hydrothermal solution. During the hydrothermal reaction the MoS2 is oxidized by [Ag(NH3 )2 ] +, and parts of the MoS2 layers are removed in the form of (NH4 )2 MoO4 . The Ag NCs are found to be uniformly dispersed on the CNTs-MoS2 . The fabricated composites (CNTs-MoS2 –Ag) exhibit excellent catalytic performances in the antibacterial tests under illumination by visible lights. The antibacterial performance is contributed by the ultra-small Ag NCs and the brilliant photo-absorption afforded by the synergistic effects between the CNTs-MoS2 and Ag NCs.